2023
DOI: 10.1128/mbio.02280-22
|View full text |Cite
|
Sign up to set email alerts
|

Emergence and Potential Extinction of Genetic Lineages of Human Metapneumovirus between 2005 and 2021

Abstract: Human metapneumovirus (HMPV) is one of the major causative agents of human respiratory tract infections. Monitoring of virus evolution could aid toward the development of new antiviral treatments or vaccine designs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 37 publications
0
14
0
Order By: Relevance
“…HMPV can be categorized in genotypes A and B, which were initially split into four sublineages: A1, A2, B1, and B2 ( 8 ). Viruses from the A1 sublineage have not been detected since 2006, while viruses from the other sublineages have continued to circulate and evolve, resulting in the emergence of newly described sublineages ( 9 ). For instance, in recent years, the circulation of viruses with a duplication in the attachment gene (G) of either 111 or 180 nucleotides (nt) was reported.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…HMPV can be categorized in genotypes A and B, which were initially split into four sublineages: A1, A2, B1, and B2 ( 8 ). Viruses from the A1 sublineage have not been detected since 2006, while viruses from the other sublineages have continued to circulate and evolve, resulting in the emergence of newly described sublineages ( 9 ). For instance, in recent years, the circulation of viruses with a duplication in the attachment gene (G) of either 111 or 180 nucleotides (nt) was reported.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, in recent years, the circulation of viruses with a duplication in the attachment gene (G) of either 111 or 180 nucleotides (nt) was reported. These viruses all belonged to the newly defined lineage A2.2.2 ( 9 13 ).…”
Section: Introductionmentioning
confidence: 99%
“…The aim of this study was to analyse the hMPV sequences obtained in East Japan in 2018 to 2022, before and after the COVID-19 pandemic, focusing on nearly complete The 180-nt and 111-nt duplications in the G gene of subgroup A2c (also named A2b2) were first reported in Spain and Japan (7)(8)(9)(10). The dominance of these viruses, especially A2c111nt-dup, is a recent global trend (7,11,13,14,27). Although A2c180-dup was not seen after 2018, it was reported that viruses carrying this G gene duplication caused lower respiratory tract infections (LRTI) in adults, possibly due to its immune evasion mechanism (28).…”
Section: Discussionmentioning
confidence: 99%
“…Although A2c180-dup was not seen after 2018, it was reported that viruses carrying this G gene duplication caused lower respiratory tract infections (LRTI) in adults, possibly due to its immune evasion mechanism (28). In Europe, hMPV circulation ebbed in 2020 due to COVID-19, but it re-emerged in and after 2021, and the most frequently detected clade was A2c111nt-dup (11,13). A2c111nt-dup was detected in 2017 to 2019; however, because of COVID-19, hMPV was not seen in 2020 to 2021 in Fukushima, East Japan (15).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation